(untitled) (Nigerian Journal of Pharmaceutical Research, 2020)
Background Lipophilicity is a crucial physicochemical parameter that predicts in vivo pharmacokinetics and should be reliably estimated in early stage drug discovery to reduce incidence of attrition. Previous methodologies for its measurement often lead to technically incorrect decisions due to simplistic architecture and poor biomimetic attributes. Significantly, a certain seed oil, used for biomembrane modelling on planar chromatographic platform, was reported to be sufficiently biomimetic and fit for purpose. Objectives To evaluate olive oil (OL) and olive-castor oil (OL-C) equi-mixture as lipids for biomembrane simulation on planar chromatographic platform. Material and Method Retention behavior of nabumetone, a model compound was used to optimize these potential lipid membranes using a thin film engineered from 5% Liquid paraffin (LP) as benchmark, while halofantrine, nabumetone , α-naphthol and β-naphthol representing varying molecular polarities, were used for validation studies. The validation involved 2-way analysis of variance (ANOVA) associated with variability in Basic lipophilicity parameter (Rmw), and Specific hydrophobic surface area (SHSA) for the optimized surfaces, relative to LP and octadecylsilane (ODS) Further validation entailed correlation of the lipophilicity descriptor i.e. isocratic chromatographic hydrophobicity index (ICHI) on OL, OL-C, ODS and LP with experimental Log P(octanol/water). Results Optimized film thicknesses were produced by 5% OL and 1.25% OL-C (p > 0.05). The 2-way ANOVA revealed great variability in performance characteristics of the surfaces (p < 0.0001), and the new surfaces also gave poorer correlation with Log P values (R2= 0.502 and 0.449 respectively). Conclusion The 1.25 % OL-C demonstrated a higher biomimetic attribute and warrants further validation studies to ascertain biorelevance, of lipophilicity measurement on this platform, in predicting oral drug absorption.